Immunofluorescence‐Mediated Detection of Respiratory Virus Infections in Human Airway Epithelial Cultures. Issue 6 (7th June 2022) - Gagliardi, Talita B.; Iverson, Ethan; DeGrace, Emma J.; Rosenberg, Brad R.; Scull, Margaret A.
Abstract: A diverse collection of viral pathogens target airway epithelial cells for infection, with effects ranging from mild upper respiratory tract symptoms to death of the infected individual. Among these pathogens are recently discovered and/or emergent viruses that sometimes fail to infect commonly used, immortalized cell lines and for which infection phenotypes in the respiratory tract remain unknown. Human airway epithelial cultures have been developed over the past several decades and have proven to be a useful model system in culturing hard‐to‐grow viruses and assaying various features of infection in a physiologically relevant setting. This article includes methods for the generation of well‐differentiated human airway epithelial cell cultures at air‐liquid interface that recapitulate the mucosal epithelium of the trachea/bronchus in vivo . We further detail inoculation of these cultures with respiratory viruses—specifically rhinovirus, influenza virus, and severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2)—and provide a protocol for the detection of double‐stranded RNA or viral antigen–positive cells by immunofluorescence microscopy. These techniques, together with a post‐imaging analysis, can be applied to characterize the efficiency of infection and kinetics of spread within the airway epithelium. Furthermore, these methods can be utilized in conjunction with antibodies against cellular targets to determine cell tropism and colocalization with specific host factors during infection. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Generation of human airway epithelial cultures at air‐liquid interface (HAE‐ALI) Basic Protocol 2 : Viral inoculation of HAE‐ALI Basic Protocol 3 : Immunofluorescence (IF)‐based detection of infected cells in HAE‐ALI